Financiamento da assistência farmacêutica e disponibilidade de medicamentos básicos no município de Belo Horizonte. - Ana Emília de Oliveira Ahouagi (2022)
Medicines are present in various stages of health care, directly affecting their resolution and, therefore, access to them must be guaranteed in universal health systems. The Unified Health System (SUS) includes policies that seek to strengthen access to medicines, especially essential ones, which aim to meet most of the population's health needs. An important strategy for achieving this objective has been the adoption of the National List of Essential Medicines (RENAME), which defines the organization and form of access to outpatient medications in the SUS. An important strategy for achieving this objective has been the adoption of the Relação Nacional de Medicamentos Essenciais (RENAME - National List of Essential Medicines) which defines an organization and a form of access to outpatient medication in the SUS. Primary Health Care (PHC) is the level of care in which users are assisted to monitor their most prevalent health conditions. Thus, the availability of medicines in the services that make up the PHC must occur in a timely manner, in adequate quantity and quality. The demands for medicines in the PHC are met through Basic Component of Pharmaceutical Assistance (CBAF - Basic Component of Pharmaceutical Services), and, for this, resources from the three spheres of government are provided for their support. Despite having specific funding forecasts, the values are not updated, and the availability of medicines in PHC may be insufficient and accessible. The city of Belo Horizonte, Minas Gerais (BH/MG) has 152 primary healthcare units, and all of them have a pharmacy to serve the population. The present study evaluated the relationship between CBAF funding and the availability of drugs in APS pharmacies in BH/MG, from 2018 to 2020. For this, the amounts agreed upon for financing the CBAF in the municipality were obtained according to the forecast of counterparts under the responsibility of the Union, State and Municipality described in the legislation in each year, and the resources invested by the municipal management in the acquisition of the component items were verified. The availability of CBAF drugs in the 152 PHC pharmacies was verified by registering them in the computerized dispensing system during the period studied and the average of the values obtained was calculated. The results show that the agreed amounts for CBAF financing to the municipality were R$ 28,376,861.82 in 2018, R$ 28,432,741.25 in 2019 and R$ 29,047,414.65 in 2020. These values are lower than the investments made by the municipality with the acquisition of CBAF items in the period, with a deficit of R$ 11,474,977.13, R$ 18,768,269.64, R$ 21,946,207.53 in 2018, 2019 and 2020 respectively. The availability of CBAF drugs in APS pharmacies was 88.71% in 2018, 94.01% in 2019 and 92.22% in 2020. With the results, it is concluded that the planned resources were insufficient for the acquisition of CBAF items in all the years studied, forcing the municipal management to make investments greater than its counterpart. This situation of imbalance in the allocation of resources between the spheres of government and the lack of resources to finance the CBAF represents an important risk for the availability of medicines in public pharmacies within the scope of the PHC, and it is urgent to update the values agreed with the forecast of readjustments annual.